“We Want Good Education for All of Us” – A Participatory Quality Improvement Approach - Holderried, Friederike; Krejci, Christine; Holderried, Martin; Lammerding-Koeppel, Maria; Loda, Teresa; Zipfel, Stephan; Herrmann-Werner, Anne (Frontiers in Medicine, 2022)
Introduction In ever changing conditions, medical faculties must face the challenge of preparing their medical students as best as possible for the demands of their future work. This requires involving all stakeholders, especially medical students in the constant redefinition of medical curricula. Using the idea of “Communities of Practice” as conceptual framework, this study looks at semester spokespeople as an example for participatory quality management. Methods We conducted focus-group interviews with semester spokespeople at a German medical faculty. Data was recorded, transcribed, and analysed using MAXQDA. The interviews were analysed using meaning condensation method. Results Eleven out of 48 semester spokespeople took part. We found seven topics that fell within three main categories: 1) role of the semester spokesperson, 2) role of the fixed meeting, and 3) contact and commitment. Communities of Practice principles could be aligned to topics and categories. Discussion The idea of semester spokespeople based on the concept of Communities of Practice are useful in the quality management processes of a medical school and lead to greater involvement of medical students, identifying their needs. The reciprocal commitment among all stakeholders fosters mutual understanding and collaboration. Future studies could investigate the underlying motivational factors of dedicated students and how to transfer these characteristics to a larger cohort.